(untitled) (Andamios, Revista de Investigación Social, 2011)
To Hegel the self-reflexivity of the reason is one of the principles of philosophy; it’s what mainly determinates the rational thinking, and it’s constitutive of the philosophic thinking for itself. It is worth noting the need of the self-reflection of the reason as the foundation of Hegel’s philosophic systematization, and, according to him, there would not be any philosophic reflection without it. The article approaches: 1) The relationship between the reality and the need of the self-reflective reason with the concept and function of the human thinking in general, and with the philosophic thinking as logical thinking; 2) its relationship with the problem of the philosophic determination of the “philosophical science” concept with the philosophical knowledge in general, and with the method; and 3) finally, it provides some elements about the relevance of the reason upon which is based the present.